Comparison between different advanced cannulation techniques for difficult biliary cannulation: a systematic review with a meta-analysis - Wang, Liangjing; Wang, Limin; Huang, Nan; Li, Tian; Shi, Xiaohua; Zhu, Qilin (Frontiers in Medicine, 2024)
We are submitting an original contribution entitled Comparison between different advanced cannulation techniques for difficult biliary cannulation: a systematic review with meta-analysis to Front Med. Corresponding author Tian Li is a member of Cochrane Collaboration, the most authoritative institution for evidence-based medicine.  The current manuscript represents the relatively high representative population cohorts (RCT) in the relevant area.  This meta-analysis provides up-to-date evidence on the the efficacy and safety of double guide wire technique and other techniques (persistent standard cannulation techniques, transpancreatic sphincterotomy, pancreatic duct stenting) in the post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis of difficult biliary cannulation.  We find that the success rate of cannulation ranked from transpancreatic sphincterotomy, double guide wire technique to persistent standard cannulation techniques. The success rate of cannulation in the double guide wire technique was much higher than persistent standard cannulation techniques [RR＝1.37，95% CI (1.05，1.79), P=0.02], while was lower than transpancreatic sphincterotomy [RR＝0.89，95% CI (0.81，0.97), P=0.01]. Thus, we advocate that early prevention and early intervention with transpancreatic sphincterotomy in the post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis of difficult biliary cannulation and the general population requires attention from the health policy makers. There is no redundant, duplicate, or pre-publication.